Multiscale Modeling of Carbon Nanotube Bundle Agglomeration inside a Gas Phase Pyrolysis Reactor. (18th May 2017) - Hou, Guangfeng; Ng, Vianessa; Xu, Chenhao; Zhang, Lu; Zhang, Guangqi; Shanov, Vesselin; Mast, David; Kim, Wookyun; Schulz, Mark; Liu, Yijun
ABSTRACT: Carbon nanotube (CNT) sock formation is required for the continuous synthesis of CNT thread or sheet using the gas phase pyrolysis method. Nanometer diameter CNTs form and are carried along the reactor tube by gas flow. During the flow, the CNT stick to each other and form bundles of about 10-100 nm diameter. Coupling of the CNT bundles in the flow leads to the formation of a centimeter diameter CNT sock with a wall that is hundreds of nanometers thick. Understanding the multiscale phenomena of sock formation is vital for optimizing the CNT synthesis and manufacturing process. In this work, we present a multiscale model for the CNT bundle agglomeration inside a horizontal gas phase pyrolysis reactor. The interaction between CNT bundles was analyzed by representing the attraction forces between CNTs using a discrete phase modeling method. Flow in the synthesis reactor was studied using a computational fluid dynamics (CFD) technique with multiphase flow analysis. A model was proposed to represent the coupling between CNT bundles and the gas flow. The effect of different CNT bundles on the agglomeration phenomenon was analyzed. The modeling results were also compared with experimental observations.